Sarcocornia fruticosa and Spartina maritima as heavy metals remediators in an European southwestern salt marsh (Ria Formosa, Portugal) - F. G. M. Silva, Manuela (2015)
Salt marshes are transition zones between land and sea, exposed to several sources of different pollutants, including heavy metals, which tend to be accumulated in sediments. Halophyte vegetation which colonises sediments affects retention and biovailability of the pollutants that reach salt marsh areas. The accumulation capacity and the pattern of metal distribution in salt marsh plant tissues vary among plant species, and with sediment characteristics. The aim of this study was to survey the behaviour of Spartina maritima and Sarcocornia fruticosa on heavy metals contents and distribution amongst sediment and plant tissues in an European Southwestern lagoon (Ria Formosa, Portugal). Both species could fix metals from the surrounding belowground environment and accumulate them mainly in roots (and in rhizomes for S. maritima). Metal translocation to aerial organs was residual. S. maritima acted as a more effective metal stabiliser than S. fruticosa.